2011
DOI: 10.1002/jbm.b.31848
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of green tea catechin α‐tricalcium phosphate combination enhances bone repair in rat skull defects

Abstract: The combination of α-TCP particles and 0.2 mg EGCG stimulates maximum bone regeneration in rat calvarial defects, and this combination would be potentially effective as bone graft material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 54 publications
1
36
0
3
Order By: Relevance
“…In addition, EGCG has been demonstrated to improve the bone microstructure and quality in aged, orchidectomized rats (17). Rodriguez et al (18) found that a combination of α-tricalcium phosphate particles and EGCG effectively stimulated bone regeneration. Furthermore, in vitro tests revealed that EGCG increased the formation of mineralized bone nodules by human osteoblast-like cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EGCG has been demonstrated to improve the bone microstructure and quality in aged, orchidectomized rats (17). Rodriguez et al (18) found that a combination of α-tricalcium phosphate particles and EGCG effectively stimulated bone regeneration. Furthermore, in vitro tests revealed that EGCG increased the formation of mineralized bone nodules by human osteoblast-like cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, MAR is a more dynamic and objective bone histomorphometric marker that considers the time-course bone remodeling activity, and relies on two very distinct fluorescent colors (red versus green). 27,29 As such, high MAR values (6-8 mm/day) were expected for the autograft.…”
Section: Discussionmentioning
confidence: 95%
“…The distance between mineral apposition layers was measured at the interface between the native bone and the implanted scaffold (INBS), both anteriorly, posteriorly, medially, and laterally with Nikon NIS Elements software tools. 27 The mean distance of the four regions was subject to statistical analysis and the overall mean distance was calculated for each rat. The mineral apposition rate (MAR) at INBS or bone healing/ regeneration was calculated for 8 and 12 weeks by dividing the overall mean distance by the interlabeling period of 32 and 60 days, respectively.…”
Section: Assessing Mineral Apposition Rate By Fluorescence Microscopymentioning
confidence: 99%
“…These findings are confirmed by micro-CT-based analysis and histological evaluation. An earlier report showed that -TCP particle implantation resulted high density areas at the defect margin and between the particles 17) . Moreover, collagen implantation resulted sporadic calcification in the defects 15) .…”
Section: Discussionmentioning
confidence: 93%